Ameloblastoma: A 16-year clinicopathological study on Goan population - Karla Maria Carvalho; Anita Dhupar; Anita Spadigam; Shaheen Syed (Indian Journal of Pathology and Microbiology, 2017)
Background: Ameloblastoma is a benign slow growing tumor of odontogenic origin composed of epithelial cells that resemble enamel forming cells namely the ameloblasts however these lesional cells do not differentiate to produce enamel. They are locally aggressive and can cause severe abnormalities of the face and jaw. Aim: This study aimed to correlate the incidence and recurrence rates of ameloblastoma to the different clinical and histopathological parameters. Methods: A study on ameloblastomas in the Goan population for 16 years (1999–2014) was carried out. Archived documented data of surgically treated cases of ameloblastomas were used in this study. Results: It was revealed that out of 52 cases of ameloblastomas, a male preponderance was seen. Age predisposition was seen to favor the third-fourth decade, the most common site was the posterior aspect of lower jaw for new and recurrent cases. Conclusion: The study highlights, the possible etiological role of location influencing the incidence and recurrence rates of ameloblastomas.